Replication and Spread of Oncolytic Herpes Simplex Virus in Solid Tumors - Bangxing Hong; Upasana Sahu; Matthew P. Mullarkey; Balveen Kaur (Viruses, 2022)
Oncolytic herpes simplex virus (oHSV) is a highly promising treatment for solid tumors. Intense research and development efforts have led to first-in-class approval for an oHSV for melanoma, but barriers to this promising therapy still exist that limit efficacy. The process of infection, replication and transmission of oHSV in solid tumors is key to obtaining a good lytic destruction of infected cancer cells to kill tumor cells and release tumor antigens that can prime anti-tumor efficacy. Intracellular tumor cell signaling and tumor stromal cells present multiple barriers that resist oHSV activity. Here, we provide a review focused on oncolytic HSV and the essential viral genes that allow for virus replication and spread in order to gain insight into how manipulation of these pathways can be exploited to potentiate oHSV infection and replication among tumor cells.